Spectral fiber dosimetry with beryllium oxide for quality assurance in hadron radiation therapy. (4th February 2022) - Metzner, E.; Bäumer, C.; Behrends, C.; Dammene Debbih, A.; Döhler, D.D.; van Goethem, M.J.; van der Graaf, E.R.; Kahle, P.; Lühr, A.; Teichmann, T.; Timmermann, B.; Weinberger, D.; et al.
Abstract: Using the radioluminescence light of solid state probes coupled to long and flexible fibers for dosimetry in radiotherapy offers many advantages in terms of probe size, robustness and cost efficiency. However, especially in hadron fields, radioluminophores exhibit quenching effects dependent on the linear energy transfer. This work describes the discovery of a spectral shift in the radioluminescence light of beryllium oxide in dependence on the residual range at therapeutic proton energies. A spectrally resolving measurement setup has been developed and tested in scanned proton fields. It is shown that such a system can not only quantitatively reconstruct the dose, but might also give information on the residual proton range at the point of measurement.